Bioacoustics of poorly known Poecilimon taxa (Insecta: Orthoptera: Tettigoniidae) with redescriptions of P. pechevi and P. stschelkanovzevi - Chobanov, Dragan P.; Sevgili, Hasan; Heller, Klaus-Gerhard (Zootaxa, 2020)
The genus Poecilimon has been object of several studies dealing with its systematics, sound communication and evolution. Yet, published data contradict in the classification, while many taxa are still insufficiently known. In the present study we supplement the knowledge of 13 poorly known species and one additional subspecies with data on their sound communication and/or morphology. Most species concerned here are classified within two acoustic groups. First group includes P. celebi, P. obtusicercus and P. toros, showing typical characteristics of the P. syriacus group. Second group is more heterogeneous. Among that, P. pechevi, P. armeniacus, P. harveyi, P. guichardi, P. haydari, P. doga, P. davisi and P. excisus present a song pattern similar to that of P. ampliatus. In addition, P. ataturki is also quite similar in basic song structure to the latter but differs in its fine song structure. Poecilimon stschelkanovzevi, with unclear relationships, is described morphologically in detail. The present study provides hints for solving some disagreement between recent revisions, proposing unification of the Poecilimon celebi with P. syriacus group and opening discussion based on close relationships of the groups ampliatus, armeniacus, davisi, luschani and the species P. guichardi on one hand, while the complex P. ataturki/glandifer shows significant differences on the other. The acoustic peculiarities of the ampliatus group allies are discussed in an evolutionary light.